Analysis of public interest in the recreational sport of gateball in tabalong district - Setiawan, Yoga Rudi; Rahmadi, Rahmadi; Kahri, Ma'ruful (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
This study aims to analyze the interest of the Tabalong Regency community in the recreational sport of gateball, focusing on external (social support and facilities) and internal (knowledge, skills, and physical condition) factors. The research method used a quantitative descriptive approach with data collection techniques through questionnaires distributed to 16 espondents. The results showed that community interest in gateball was in the moderate to high category, with external factors contributing 37.5% and internal factors such as physical condition reaching 43.75%. However, the community's knowledge and skills are still diverse, with an even distribution in the low, medium, and high categories (31.25% each). These findings indicate that increasing interest in exercise requires a holistic approach, including the provision of adequate facilities, education and community strengthening. The limitations of this study lie in the limited number of samples and have not examined cultural/local factors, so further research is recommended to broaden the scope of respondents and explore additional aspects that may be influential. With the implementation of the right strategy, gateball sports have great potential to develop as a popular recreational activity in Tabalong Regency This study recommends collaboration between the government, sport players, and the community to increase participation in the sport of gateball.